THE ROLE OF POLITICAL CONNECTIONS IN MODERATING THE EFFECT OF BOARD DIVERSITY ON FINANCIAL DISTRESS - Prihatiningtias, Yeney Widya; Adiwicaksana, Surya (Journal of Applied Finance and Accounting, 2024)
This research aims to examine the role of political connection in moderating the effect of board gender diversity and board size on financial distress. A sample of 46 banking companies listed in Indonesia Stock Exchange between during the 2021-2023 period was selected using a purposive sampling method. Panel data regression were used for data analysis. The results of the research exhibit that board of commissioner gender diversity has no effect on financial distress; board of director gender diversity has a positive effect on financial distress; and board size has a negative effect on financial distress. Political connections cannot moderate the effect of gender diversity, but can moderate the negative effect of gender diversity and the positive effect of board size on financial distress. This finding, as such, can provide insights for corporate management and regulators to determine the most effective corporate board design to improve the companies financial performance and avoid financial distress. Keywords: Board diversity; board size; corporate governance; political connection; financial distress